ANALISIS PEMBELAJARAN DARING DI MADRASAH ALIYAH AN-NUR BENER MERIAH - Ahmad Yunus Mokoginta Harahap (IAI Darussalam, 2020)
Since the issuance of the circular letter of the Minister of Education and Culture on March 24, 2020, regarding the implementation of education in the emergency period of the spread of Covid-19, the learning process has been carried out throughout Indonesia online. This study aims to determine the implementation and process of making online learning policies, the media used in online learning, and the assessment carried out in online learning at Madrasah Aliyah An-Nur Bener Meriah. The research method used in this research is descriptive qualitative research, data collection techniques are carried out by means of observation, interviews and documentation, while the data is analyzed using qualitative analysis. This study resulted in findings in the form of the implementation of online learning at Madrasah Aliyah An-Nur Bener Meriah since April 2020 after a discussion was held by the head of the madrasa with stakeholders. There are several media used in online learning at Madrasah Aliyah An-Nur Bener Meriah, including Whatsapp, Google Classroom, Zoom Meeting. Assessment is carried out in a formative, fair, objective and transparent manner to get feedback from students and parents.